Electricity load forecasting for smart home - Lin, James Rizhong (Nanyang Technological University, 2022)
Due to expanding global human population, the demand for electricity is ever increasing. Energy is difficult and expensive to store in bulk, so to ensure the demand can be met by energy suppliers, it is important to be able to forecast electricity load with high accuracy. Electricity load forecasting (ELF) is a significant activity in topics such as power systems planning & operation. With the adoption of clean and sustainable energy, together with the need for more efficient and reliable power grids, there is a push towards Smart Grid. ELF is one of the relevant procedures made possible by Smart Grids.